ENTREPRENEURIAL UNIVERSITY AND THE TRIPLE HELIX THEORY - Nikita V. Golovko; Valeriya V. Degtyareva; Svetlana A. Madyukova (Высшее образование в России)
The paper aims to analyze the features of interpretation of the notion of entrepreneurial university within the Triple Helix theory in the light of the capitalization of knowledge problem. Following the traditional understanding (B. Clark) the notion of entrepreneurial university connects the capitalization of knowledge with the external socioeconomic factors. At the same time, within the Triple Helix theory (H. Etzkowitz et al.) this notion gives a possibility to evaluatean internal dynamics of the capitalization of knowledge based on the analysis of the epistemological and cognitive roots of knowledge production.